Ritual Sosial Klub Motor â€œSatudarahâ€ Chapter Bali - Robert, Yohanes Julian; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The aim of this research is to analized the various dimensions of social rituals found in the motorcycle club Satudarah Maluku Bali chapter. Satudarah Maluku is a motorcycle club that has characteristic of Malukunese culture in social life among its members, making Satudarah Maluku become an interesting research object to studied from sociological perspective. This research used Social Ritual theory from Dick Hebdige & John Clarke to analyze various meanings of social ritual dimension contained in motorcycle club Satudarah Maluku Bali chapter. Various dimensions have real meaning that can be divided into four main elements namely the meaning of social ritual dimensions as a form of resistance, symbols, identity, and styles in which is divided into various forms of style such as bricolage and homology. Furthermore, this research uses descriptive-explanative research method using qualitative approach. Various data collection is applied to support the success and accuracy of data in this study. Through a series of research methods that have been applied, it is found that some research results reveal a covert resistance to the stereotypes from ordinary people to motor clubs, the various dimensions of social rituals that imply a variety of symbolic meanings, and identity as unifier in club kinship ties, and an acknowlegde of various meaning of styles in various dimensions of social rituals undertaken by motorcycle club Satudarah Maluku Bali chapter. keywords: social ritual, motorcycle club, Satudarah Maluku